Where are the marathon Girls?: An Analysis of Female Representation in the Brazilian ICPC Programming Marathons - Irion, Crishna; Theodoro, Luiz Claudio; Silva, Flávio de Oliveira; Pereira, João Henrique de Souza (Anais do Women in Information Technology (WIT), 2023)
Education motivated the encouragement of female participation in several areas of science and technology. Programming marathons have grown over the years and are events where programmers compete to solve coding challenges. However, despite scientific evidence that there is no intellectual difference between genders, women’s participation is relatively low. This work seeks to understand the reason for this adherence, considering the gender issue in Programming Marathons over the last years, in a real context. This work aims to understand the context of female representativeness in which the intellectual aspects do not differ in gender. Still, there is a considerable discrepancy in female belonging.